2012
DOI: 10.1101/gr.131474.111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of mutations in mutant lineages selected following fast-neutron irradiation mutagenesis of Arabidopsis thaliana

Abstract: Ionizing radiation has long been known to induce heritable mutagenic change in DNA sequence. However, the genomewide effect of radiation is not well understood. Here we report the molecular properties and frequency of mutations in phenotypically selected mutant lines isolated following exposure of the genetic model flowering plant Arabidopsis thaliana to fast neutrons (FNs). Previous studies suggested that FNs predominantly induce deletions longer than a kilobase in A. thaliana. However, we found a higher freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
175
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(191 citation statements)
references
References 43 publications
14
175
2
Order By: Relevance
“…Finally, mutations that exhibited a heterozygous pattern (e.g., where 20%-80% of reads showed a base different from the reference base) or where there was insufficient coverage in G0 or G10 were also excluded from the final mutation lists. Our previous studies confirmed that ;100% of the mutations detected by the above described multistep variant detection pipeline were real (Jiang et al 2011;Belfield et al 2012). Using this pipeline, we identified 102 and 52 mutations in G10 saline soil and control samples, respectively (Supplemental Tables S2, S3).…”
Section: Salt Content Determinationsupporting
confidence: 58%
See 2 more Smart Citations
“…Finally, mutations that exhibited a heterozygous pattern (e.g., where 20%-80% of reads showed a base different from the reference base) or where there was insufficient coverage in G0 or G10 were also excluded from the final mutation lists. Our previous studies confirmed that ;100% of the mutations detected by the above described multistep variant detection pipeline were real (Jiang et al 2011;Belfield et al 2012). Using this pipeline, we identified 102 and 52 mutations in G10 saline soil and control samples, respectively (Supplemental Tables S2, S3).…”
Section: Salt Content Determinationsupporting
confidence: 58%
“…The transition/transversion (Ti/Tv) ratio of single base substitutions accumulating in A. thaliana MA lineages exposed over multiple successive generations to soilsalinity stress (;1.7) is different from that of control MA lineages (;2.5) (Fig. 1C), but similar to that of mutations accumulated in in vitro regenerant or irradiated A. thaliana lineages (Jiang et al 2011;Belfield et al 2012). Intriguingly, the change in Ti/Tv ratio generated by salt stress in A. thaliana is similar to that generated by the environmental stress response in yeast (Shor et al 2013).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is a broader diversity of effects reported of plants treated with physical mutagens. For example, fast neutron irradiation of plants has been reported to generate genomic deletions ranging in size from less than 56 base pairs to nearly three million base pairs (Li et al 2001;Rogers et al 2009;Bolon et al 2011;Belfield et al 2012). The most common mutagen used in the development of the~3200 officially released mutant crop varieties curated in the IAEA's Mutant Variety Database (http://mvd.iaea.org/) is gamma irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…These mutations can now be identified at the whole-genome level using HTS. In A. thaliana, fast-neutron-induced mutations were revealed to be mainly base substitutions and small deletions (Belfield et al, 2012). We have previously identified the mutation spectrum of the heavy-ion beam in A. thaliana as comprising base substitutions, deletions, insertions and chromosomal rearrangements (Hirano et al, 2015).…”
mentioning
confidence: 99%